Wine tourist profiling in the Porto wine cellars: segmentation based on wine product involvement - Ramos, Vasco (2020)
This paper segments a sample of 918 Porto wine cellars visitors based on their wine product involvement. A segmentation methodology was applied to the wine product involvement of wine tourists. Three clusters were identified with high, medium and low wine product involvement levels. The relevant theoretical contribution of this study was to provide new evidence of segmentation based on product involvement studies in the wine tourism market field in an area were empirical studies still remain scarce. The findings offer managerial implications regarding the wine tourists’ identification and how to better adapt the visits. This is also the first study demonstrating wine tourist profiling and segmentation specifically applied to involvement with the Porto wine product.